2012
DOI: 10.1021/ja3031664
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenol EGCG Inhibits Amyloid Formation Less Efficiently at Phospholipid Interfaces than in Bulk Solution

Abstract: Age-related diseases, like Alzheimer's disease and type 2 diabetes mellitus, are characterized by protein misfolding and the subsequent pathological deposition of fibrillized protein, also called amyloid. Several classes of amyloid-inhibitors have recently been tested, traditionally under bulk conditions. However, it has become apparent that amyloid fibrils and oligomers assemble and exert their cytotoxic effect at cellular membranes, rather than in bulk solution. Knowledge is therefore required of inhibitor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 62 publications
(134 reference statements)
1
124
1
Order By: Relevance
“…However, although many of these compounds have been tested in mice, not all of them would be suitable for clinical use. Alternative inhibitors which could be administered to humans have included some aromatic compounds including resevatrol (a component of red wine) (Porat et al 2004, Evers et al 2009, Mishra et al 2009) and some polyphenols including (−)-Epigallocatechin 3-Gallate (EGCG) (a natural component of green tea); inhibition of fibrillogenesis was accompanied by disaggregation of fibrils and formation of non-toxic oligomers (Meng et al 2010, Engel et al 2012. Other inhibitors effective in vitro are tetracycline, congo red, ruthenium red, and organic designed 'foldamers' (Aitken et al 2003, Kumar & Miranker 2013, Zhu et al 2017.…”
Section: Inhibitors Of Iapp Fibrillogenesis: a Suitable Treatment In mentioning
confidence: 99%
“…However, although many of these compounds have been tested in mice, not all of them would be suitable for clinical use. Alternative inhibitors which could be administered to humans have included some aromatic compounds including resevatrol (a component of red wine) (Porat et al 2004, Evers et al 2009, Mishra et al 2009) and some polyphenols including (−)-Epigallocatechin 3-Gallate (EGCG) (a natural component of green tea); inhibition of fibrillogenesis was accompanied by disaggregation of fibrils and formation of non-toxic oligomers (Meng et al 2010, Engel et al 2012. Other inhibitors effective in vitro are tetracycline, congo red, ruthenium red, and organic designed 'foldamers' (Aitken et al 2003, Kumar & Miranker 2013, Zhu et al 2017.…”
Section: Inhibitors Of Iapp Fibrillogenesis: a Suitable Treatment In mentioning
confidence: 99%
“…Similarly, polyphenolic compounds, including tea polyphenols, interact with and alter lipid membranes (Blazovics et al 2000;Oku et al 2003;Chen et al 2011;Duchnowicz et al 2012;Sharma et al 2012). Indeed, it was revealed that EGCG inhibits amyloid formation less efficiently at phospholipid interfaces than in bulk solution (Engel et al 2012). Hence, it is relevant to know how polyphenolic compounds directly effect lipid membranes and how efficiently they can inhibit 'S aggregation specifically at the phospholipid membrane interface.…”
Section: Inhibitory Activity On '-Synuclein Aggregationmentioning
confidence: 99%
“…Recently, many kinds of inhibitors have been developed to prevent brillization of hIAPP, including small organic molecules, [7][8][9][10][11][12][13] peptides, [14][15][16] proteins 17 and nanoparticles. 18,19 Among these, small organic molecules have received special interest because of their high permeability through the blood-brain barrier and potentially low cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Several natural compounds have been found to prevent hIAPP brillization or to transform the mature brils into unstructured, off-pathway aggregates. 8,21,22 For example, Chen et al 23 have found that the brillation and aggregation of hIAPP is affected by trehalose in a dose-dependent manner. A low dose of trehalose inhibited the conformational transition of hIAPP.…”
Section: Introductionmentioning
confidence: 99%